Plasmid-mediated virulence in Salmonella dublin demonstrated by use of a Tn5-oriT construct. - Chikami, G K (1985)
Salmonella dublin, a serotype which causes invasive disease in cattle and humans, carries a characteristic 80-kilobase plasmid (pSDL2). We were able to cure the plasmid from a strain of S. dublin. The cured strain was avirulent for mice by either the oral or intraperitoneal route of infection. A derivative of Tn5 which contains the transfer origin of the broad-host-range plasmid RK2 (Tn5-oriT) was transposed onto pSDL2, allowing mobilization of the plasmid by an RK2 helper plasmid. Reintroduction of the pSDL2 derivative plasmid into the cured strain restored virulence, demonstrating that the plasmid is necessary for virulence. These studies also demonstrate the usefulness of the Tn5-oriT construct for genetic manipulations.